Mutation in an intervening sequence splice junction in man. - Orkin, S H (1981)
The alpha 2-globin gene of an individual with alpha-thalassemia associated with the absence of alpha 2 mRNA was cloned in bacteriophage. This mutant globin gene was normally active in transcription in vitro. The DNA sequence of the gene, however, revealed a pentanucleotide deletion within the 5' splice junction of the first intervening sequence. Following the G of the invariant G-T dinucleotide normally located within such junctions, a deletion of T-G-A-G-G was found. No other sequence abnormalities within the mutant gene were present. We speculate therefore that this deletion within the splice junction is the primary genetic defect in this individual with thalassemia and that loss of a functional splice junction results in failure of stable mRNA formation.